Detección temprana del trastorno del espectro autista y puntaje obtenido del examen de admisión en los estudiantes del centro preuniversitario de la Universidad Nacional Jorge Basadre Grohmann - Morales-Quezada, José Luis (2024)
Objective: To determine the relationship between early detection of autism spectrum disorder (ASD) and the score of the pre-university admission process CEPU-2024 of the Universidad Nacional Jorge Basadre Grohmann. Material and methods: Cross-sectional analytical study in students of the pre-university center. Non-probabilistic census-type sampling was applied. For the detection of autism spectrum disorder, Allison's 10-item AQ-10 screening instrument, adapted to Spanish by López, was applied; likewise, the score of the admission exam in cycle I of CEPU 2024 was obtained. Descriptive statistics, normality tests and Spearman's correlation statistic were applied. Results: Of 1051 participating applicants, 18.55% had autism spectrum disorder (n = 195), of whom 61.54% were female. There is a weak and negative relationship between ASD and the admission process score; that is, as early detection of ASD increases, the university admission score decreases. It is inferred that as more students with ASD are detected, there are fewer ASD entrants. But this correlation is not statistically significant (p = 0.178; r = -0.097). Conclusion: There is no relationship between early detection of autism spectrum disorder and pre-college admissions scores.